Upaya Meningkatkan Hasil Belajar Siswa dengan Menggunakan Media Audio Visual dalam Pembuatan Roti pada Siswa Sekolah Menengah Kejuruan - Rita Nanda (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The results of preliminary observations on students of Class XI Catering at SMK Negeri 3 Karang Baru indicate that there are several obstacles faced by students in the learning process. One of the obstacles is the lack of motivation and student learning outcomes in the learning material of bread making. The aim is to improve student learning outcomes and activities, as well as to find out student responses through the use of audio-visual media on bread-making materials for class XI Catering at SMK Negeri 3 Karang Baru, Aceh Tamiang. This study used classroom action research (CAR) which was carried out in 2 cycles. The subjects of this study were students of class XI Catering at SMK Negeri 3 Karang Baru, Aceh Tamiang. To obtain data in this study, tests, observations and interviews were used. The results obtained from this study are that in the initial cycle who completed classically only reached 22%, but in cycle I students who completed classically reached 56%, but increased to 89% students who completed classically in cycle II. obtained, it can be concluded that the material for making bread with audio-visual media in class XI Catering at SMK Negeri 3 Karang Baru Aceh Tamiang can run effectively and pleasantly and can improve student learning outcomes,